Thursday

April 24, 2014

April 24, 2014

Posted by **Leo** on Thursday, November 8, 2007 at 3:59pm.

Expand (5 - 2x) Squared

(5 - 2x) (5 - 2x)

5 sqrd + 5 X - 2x + -2x x 5 + -2x X -2x

so

5 Sqrd - 10x - 10x + 4X

= 5 sqrd + 4x

Am I right..thank you :-)

- Algebra -
**Reiny**, Thursday, November 8, 2007 at 5:29pmNo, you should use FOIL

F - multiply the Firsts

O - multiply the Outers

I - multiply the Inners

L - multiply the Lasts

so (5 - 2x) (5 - 2x)

= (5)(5) + (5)(-2x) + (-2x)(5) + (-2x)(-2x)

= 25 - 20x + 4x^2

**Related Questions**

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

Math33333 - Please help me! Problem: x+2 x-3 _________ - _________ 2x^2+5x+2 2x^...

Math - Can someone please check this for mistakes please? y=4(x+3)-2x y=4x+3-2x ...

math - i am having a minor difficulty i've been stuck for over an hour and don't...

Pre-Cal(Please help) - 1)(1-cos^2x)(csc x) ? Is this equal to sec x? 2) Expand...

TO KIM - can you help me with this |2x - 3|^2 - 6|2x - 3| + 5=0 I know you are ...

Algebra - Need help with this problem, 2x+y=6 solve for y 2x+y=6 subtract 2x ...

Algebra help - Find (fog)(x)and (gof)(x)if f(x)=x-x^2 and g(x)= 2x+3. Okay so I ...

math - how many times does the graph of y= 2x squared -2x+3 intersect the x-axis...

TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...